Acoustic surveys of Water Rail Rallus aquaticus over-wintering on Alderney. Issue 2 (2nd April 2020) - Hart, Justin D.
ABSTRACT: A 'call count' survey of Water Rails Rallus aquaticus, using broadcast vocalizations to elicit a response, was carried out on Alderney over two consecutive winters. The species was found to be widespread on the island, with 34 birds found in both winters. Most, 62% in each winter, occurred in habitats associated with water, but 38% unexpectedly occupied drier habitat. The survey presents new information on Water Rail abundance, distribution and habitat use on the island, and indicates that the species does not always require access to wet ground in winter.